The Role of Cell Cycle Machinery in Ischemic Neuronal Death - Iyirhiaro, Grace O. (Université d'Ottawa / University of Ottawa, 2013)
Ischemic stroke occurs as a result of a lack or severe reduction of blood supply to the brain. Presently therapeutic interventions are limited and there is a need to develop new and efficacious stroke treatments. To this end, a great deal of research effort has been devoted to studying the potential molecular mechanisms involved in ischemic neuronal death. Correlative evidence demonstrated a paradoxical activation of the cell cycle machinery in ischemic neurons. The levels and activity of key cell cycle regulators including cyclin D1, Cdk2 and Cdk4 are upregulated following ischemic insults. However, the functional relevance of these various signals following ischemic injury was unclear. Accordingly, the research described in this thesis address the functional relevance of the activation of the cell cycle machinery in ischemic neuronal death. The data indicate that the inhibition of Cdk4 protects neurons from ischemia-induced delayed death, whereas abrogation of Cdk5 activity prevents excitotoxicity-induced damage in vitro and in vivo. Examination of upstream activators of mitotic-Cdks showed that Cdc25A is a critical mediator of delayed ischemic neuronal death. Investigation of the potential molecular mechanism by which cell cycle regulators induced neuronal death revealed perturbations in the levels and activity of key downstream targets of Cdk4. The retinoblastoma protein family members, pRb and p130 are increasingly phosphorylated following ischemic stresses. Importantly, p130 and E2F4 proteins are drastically reduced following ischemic insults. Additionally, E2F1 association with promoters of pro-apoptotic genes are induced while that of E2F4 is reduced. These changes appear to be important determinants in ischemic neuronal death. Cumulatively, the data supports the activation of the cell cycle machinery as a pathogenic signal contributing to ischemic neuronal death. The development of neuroprotectant strategies for stroke has been hampered in part by its complex pathophysiology. Previous research indicated that flavopiridol, a general CDK-inhibitor, is unable to provide sustained neuroprotection beyond one week following cerebral ischemia. The potential benefit of combining flavopiridol with another neuroprotectant, minocycline, was explored. The data indicate that while this approach provided histological protection 10 weeks after insult, the protected neurons are not functional due to progressive dendritic degeneration. This evidence indicates that targeting cell cycle pathways in stroke while important must be combined with other therapeutic modalities to fully treat stroke-induced damage.
Keywords: Cell Cycle; Cell death; Neuronal death; Stroke; Cerebral Ischemia; Cdks; Cdc25; E2F4; p130; pRb; Neuroprotection; Inflammation; Flavopiridol; Minocycline; C-Myb; B-Myb; Excitotoxicity; Cdk4; Cyclin D1; Cdk5